Consistent Ipsilateral Development of the Posterior Extension of the Quadrangular Cartilage and Bony Spur Formation in Nasal Septal Deviation. (8th January 2015) - Saedi, Babak; Rashan, Ali R.; Lipan, Michael; Nayak, Jayakar V.; Most, Sam P.
Abstract : Objective: Septal spurs are exceedingly common structural deformities that contribute to nasal obstruction and often require surgical correction. The posterior extension of the quadrangular cartilage (PEQC) and its relationship with septal spurs have not been previously examined. We seek to examine the anatomic and histologic relationship of the PEQC and concurrent septal spurs in patients undergoing septoplasty. Study Design: Prospective cohort study. Setting: Facial plastic and rhinology center in tertiary hospital setting. Subject and Methods: Thirty patients with septal deviation are described in this series. The quadrangular cartilage and associated septal spur were removed en bloc from patients undergoing septoplasty. The length of the PEQC, the side of spur deviation, and the relationship of the PEQC to the spur (ipsilateral vs contralateral) were recorded. Results: The mean length of the PEQC, beyond the bony‐cartilaginous junction, was 30.06 ± 6.06 mm. The PEQC was present on the ipsilateral side of the spur deviation in all 30 patients (100%). Conclusion: At sites of septal spur formation, the quadrangular cartilage possesses an average 3‐cm extension beyond its junction with the bony components of the septum. This cartilaginous extension is exclusively found on the same side of spur deviation. These findings have implications on our understanding of the ontogeny of commonly found septal spurs and deviations, as well as treatment strategies and cartilage graft harvesting.